Comparison of antifungal activity of essential oils from different plants against three fungi. (December 2019) - Hu, Fei; Tu, Xiao-Fang; Thakur, Kiran; Hu, Fan; Li, Xiao-Li; Zhang, Ying-Shuo; Zhang, Jian-Guo; Wei, Zhao-Jun
Abstract: The antifungal activity of plant essential oils (EOs) extracted by steam distillation from seven different species (Cinnamon, Anise, Clove, Citronella, Peppermint, Pepper, and Camphor) was investigated. Three common fungi were isolated from moldy wheat bread, which were identified as Aspergillus niger, A. oryzae, and A. ochraceus . The antifungal activity of anise, peppermint, clove, cinnamon, pepper, citronella, and camphor EOs from seven different spices was confirmed by agar diffusion assay against three fungi. Among all the EOs, the cinnamon EO showed the highest antifungal activity for all the fungi strains with the largest inhibition zone at the concentration of 800 mg/mL and lowest MIC ranging from 0.0625 to 0.125 mg/mL, followed by clove EO. The remaining EOs exerted moderate inhibitory effects. Further research indicated the substantial inhibitory activities of cinnamon and clove EOs on mycelial growth and spore germination in a dose-dependent manner. Further, the in vivo inhibitory activity of selected EOs on naturally infected bread demonstrated that cinnamon and clove EOs can as be used as natural antifungal agents. Graphical abstract: Image 1 Highlights: A. niger, A. oryzae and A. ochraceus were isolated from the moldy wheat bread. Among the seven edible spices EOs, cinnamon and clove EOs exhibited the highest antifungal activity. Cinnamon and clove EOs inhibited the mycelial growth and spore germination of three tested fungi. Cinnamon and clove EOs effectively controlled the natural mold spoilage and extend the shelf-life of wheat bread.